ANALISIS HUKUM TERHADAP PEMBELI CESSIE (CESSIONARIS) ATAS PENGUASAAN OBJEK HAK TANGGUNGAN (CONTOH KASUS: PENETAPAN PENGADILAN NEGERI MEMPAWAH NOMOR 130/PDT.P/2018/PN.MPW) - Jessica Priscilla Simanungkalit; Hasni Hasni (Fakultas Hukum Universitas Tarumanagara, 2019)
Mortgage rights can be said as collateral for land to pay off certain debts. Mortgage can be transferred through cessie. A cessie is a form of transfer of receivables on behalf of a creditor holding a mortgage that relates only to an agreement to hand over something to another party. Cessionary cannot directly have the object of Mortgage because the legal system in Indonesia that recognizes the prohibition of beding. In this case, the cessionary named Niko Septian made a request to the Mempawah District Court to request the name of the certificate so that the object of Dian Romadhon Siagian's debt security belonged to the cessionary. An application submitted by Niko Septian was granted by the District Court. Settlement that can be done so as not to violate the system of prohibition belonging to the beding is able to register the object of collateral receivables to the auction hall.